Comparing the Clinical Efficacy of Plantago Major with Chlorhexidine Mouthwash in Patients with Gingivitis - A Clinical Study - Priyadharshini; S. Elanchezhiyan; Rajkumar Daniel; K. Mohamed Adhil; K. Vennila; Gayathri Priyadharshini (Indian Journal of Integrative Medicine, 2023)
Background: India has a very long history of using herbal drugs for treating a number of diseases. The herbal drugs have made their importance felt in the past few decades whose prevalence is continuously increasing in both developing and developed countries due to their natural origin and lesser side effects. Therefore, the aim of the present study was to evaluate and compare the clinical efficacy of Plantago major with chlorhexidine mouthwash in patients with gingivitis. Materials and Method: 30 medically healthy individuals with gingivitis reporting to the Dental College was randomly selected. Scaling was performed for the patients and they were randomly allotted to control and test groups respectively. Group-I (Control) 15 patients were advised to rinse with Chlorhexidine mouthwash (0.2%- 2ml+6ml water (1:3 dilution) =8ml) for 21 days. Group-II (Test) 15 patients were advised to rinse with Plantago major (Mother tincture 1M- 2ml+ 6ml distilled water (1:3 dilution) =8ml) for 21 days. Plaque index, gingival index and gingival bleeding index was recorded at baseline and after 21 days. Results: On Intragroup comparison, statistically significant result was obtained when baseline and 21 days clinical parameters where evaluated. On Intergroup comparison the results obtained were not statistically significant. This shows that Plantago major is as effective as Chlorhexidine in reducing inflammation. Conclusion: Plantago major promises to be an effective alternative for chlorhexidine mouthwash. Further long term studies must be conducted to evaluate its effects on systemic health.